ErbB4 Preserves Blood-Brain Barrier Integrity via the YAP/PIK3CB Pathway After Subarachnoid Hemorrhage in Rats - Qian, Huan; Dou, Zhangqi; Ruan, Wu; He, Pingyou; Zhang, John H.; Yan, Feng (Frontiers in Neuroscience, 2018)
Studies have suggested that blood-brain barrier (BBB) disruption contributes to the pathogenesis of early brain injury after subarachnoid haemorrhage (SAH). Activation of the receptor tyrosine kinase ErbB4 can cause intramembrane proteolysis and release a soluble intracellular domain (ICD) that modulates transcription in the nucleus. This study was carried out to investigate the potential roles of ErbB4 in preserving BBB integrity after experimental SAH, as well as the underlying mechanisms of its protective effects. Endovascular perforation was used to prepare a rat SAH model. The SAH grade, neurological score, brain edema and BBB permeability were evaluated after surgery. Immunohistochemistry was used to determine the localization of ErbB4 and yes-associated protein (YAP). ErbB4 activator Nrg1 isoform β1 (Nrg1β1), Specific ErbB4 siRNA, YAP siRNA and PIK3CB specific inhibitor TGX 221 were used to manipulate the proposed pathway. The expression levels of ErbB4 ICD and YAP were markly increased after SAH. Double immunohistochemistry labeling showed that ErbB4 and YAP were expressed in endothelial cells and neurons. Activation of ErbB4 by Nrg1β1 (dosage 150 ng/kg) treatment promoted the neurobehavioral deficit, alleviated the brain water content and reduced albumin leakage 24 and 72 h after SAH. ErbB4 activation significantly promoted YAP and PIK3CB activity and increased the expression of tight junction proteins Occludin and Claudin-5. Depletion of ErbB4 aggravated neurological impairment and BBB disruption after SAH. The beneficial effects of ErbB4 activation were abolished by YAP small-interfering RNA and specific PIK3CB inhibitor. Activation of ErbB4 improved neurological performance after SAH through the YAP/PIK3CB signaling pathway, this neuroprotective effects may associated with BBB maintenance.